Analysis of Investment Plans Supporting Industry 4.0 among Small and Medium-Sized Enterprises in Poland - Alina RYDZEWSKA (Communications of International Proceedings, 2020)
The aim of this study is to analyse investment plans supporting Industry 4.0 among small and medium-sized enterprises in the industrial sector in Poland. The research carried out allowed to conclude that the majority of enterprises do not have specific plans for investments supporting Industry 4.0. However, in the case of responses that were definite, the largest part was “probably yes”. Considering the investment plans of enterprises from the point of view of the size criterion, micro enterprises (turnover up to or equal to EUR 2 million) constitute a group characterised by less definite investment plans. Taking into account the duration of operation (number of years), the statistical analysis did not indicate a group of enterprises that differs from the others. In turn, the results of the analysis concerning the investment plans of enterprises from various provinces are not clear. The initial analysis showed the following provinces: Pomeranian, Podlaskie, Łódź, Greater Poland, of which companies generally declared plans to increase investment outlays. However, the statistical analysis did not show any differences. The PKD (Polish Classification of Business Activities) section, in which most respondents intend to make investments related to Industry 4.0 is the production of finished metal products.
Keywords: Industry 4.0; investment plans; small and medium-sized enterprises; statistical analysis.